The lancet countdown on health and plastics - Landrigan, Philip J.; Dunlop, Sarah; Treskova, Marina; Raps, Hervé; Symeonides, Christos; Muncke, Jane; Spring, Margaret; Stegeman, John; Almroth, Bethanie Carney; Chiles, Thomas C; Cropper, Maureen; Deeney, Megan; et al. (European journal of cancer, 2025)
Plastics are a grave, growing, and under-recognised danger to human and planetary health. Plastics cause disease and death from infancy to old age and are responsible for health-related economic losses exceeding US$1·5 trillion annually. These impacts fall disproportionately upon low-income and at-risk populations. The principal driver of this crisis is accelerating growth in plastic production—from 2 megatonnes (Mt) in 1950, to 475 Mt in 2022 that is projected to be 1200 Mt by 2060. Plastic pollution has also worsened, and 8000 Mt of plastic waste now pollute the planet. Less than 10% of plastic is recycled. Yet, continued worsening of plastics' harms is not inevitable. Similar to air pollution and lead, plastics' harms can be mitigated cost-effectively by evidence-based, transparently tracked, effectively implemented, and adequately financed laws and policies. To address plastics' harms globally, UN member states unanimously resolved in 2022 to develop a comprehensive, legally binding instrument on plastic pollution, namely the Global Plastics Treaty covering the full lifecycle of plastic. Coincident with the expected finalisation of this treaty, we are launching an independent, indicator-based global monitoring system: the Lancet Countdown on health and plastics. This Countdown will identify, track, and regularly report on a suite of geographically and temporally representative indicators that monitor progress toward reducing plastic exposures and mitigating plastics' harms to human and planetary health.